2019
DOI: 10.1111/cei.13400
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the microbiota with the mucosal immune system

Abstract: Summary The field of mucosal immunology has, for the last 10 years, been largely dominated by advances in our understanding of the commensal microbiota. Developments of novel experimental methodologies and analysis techniques have provided unparalleled insight into the profound impact the microbiota has on the development and function of the immune system. In this cross‐journal review series published in Immunology and Clinical and Experimental Immunology, we aim to summarize the current state of research conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The microbiota can regulate the proliferation and differentiation of intestinal epithelial cells (IECs) and be conducive to intestinal absorption of digestible nutrients ( Lin et al, 2021 ; Chen et al, 2021a ). Moreover, intestinal flora can promote the secretion of SIgA, a very important immunoglobulin in intestinal mucosal immunity, to prevent bacterial adhesion and invasion and to maintain the integrity of the intestinal mucosal layer ( Bain and Cerovic, 2020 ). However, studies have indicated that the disturbance of intestinal microbiota may participate in the process of disease development, such as diabetes mellitus (DM), obesity, inflammatory bowel disease (IBD), cardiovascular disease (CVD), tumor, and mental diseases ( Dong et al, 2019 ; Villeger et al, 2019 ; Alvarez-Vieites et al, 2020 ; Suslov et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The microbiota can regulate the proliferation and differentiation of intestinal epithelial cells (IECs) and be conducive to intestinal absorption of digestible nutrients ( Lin et al, 2021 ; Chen et al, 2021a ). Moreover, intestinal flora can promote the secretion of SIgA, a very important immunoglobulin in intestinal mucosal immunity, to prevent bacterial adhesion and invasion and to maintain the integrity of the intestinal mucosal layer ( Bain and Cerovic, 2020 ). However, studies have indicated that the disturbance of intestinal microbiota may participate in the process of disease development, such as diabetes mellitus (DM), obesity, inflammatory bowel disease (IBD), cardiovascular disease (CVD), tumor, and mental diseases ( Dong et al, 2019 ; Villeger et al, 2019 ; Alvarez-Vieites et al, 2020 ; Suslov et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include 'Ageing and the immune system, effects of immunosenescence and clinical implications' (2017), co-edited by Birgit Weinberger and the current President of the BSI, Professor Arne Akbar, and exploring the impacts of age on the functionality of the immune system [17]. In 'Interactions of the Microbiota with the Mucosal Immune System' (2020), published jointly with CEI's sibling journal, Immunology, Vuk Cerovic and Calum Bain and Series contributors examined current understanding of the roles of microorganisms in human mucosal immunology [18]. We are equally proud of our series released in collaboration with FOCIS, 'Immune Checkpoints Inhibition: From Molecules to Clinical Application' (2020), in which the current Editor-in-Chief, Leonie Taams, also an author in the series, and Section Editor for Cancer Immunity, Tanja de Gruijl, invited a series of reviews exploring the molecular and clinical understanding surrounding checkpoint inhibitors [19].…”
mentioning
confidence: 99%
“…First, Vuk Cerovic and Calum Bain provided their wellreceived 'Interactions of the Microbiota with the Mucosal Immune System' series. 7 James Harker and Laura Pallett 8 then guided us through seven outstanding reviews exploring 'Barrier Immunity'. Eyal Amiel and Georgia Perona-Wright 9 contributed to a rapidly expanding field with the first part of their series 'Immunometabolism of Infection'.…”
mentioning
confidence: 99%
“…We published four exciting review series across 2020. First, Vuk Cerovic and Calum Bain provided their well‐received ‘Interactions of the Microbiota with the Mucosal Immune System’ series 7 . James Harker and Laura Pallett 8 then guided us through seven outstanding reviews exploring ‘Barrier Immunity’.…”
mentioning
confidence: 99%